Alveolar echinococcosis in the canton of Geneva between 2010 and 2021: a descriptive analysis (Swiss Medical Weekly, 2025)
BACKGROUND: Alveolar echinococcosis is a rare but potentially severe parasitic disease caused by the larval stage of Echinococcus multilocularis, endemic in many countries in the northern hemisphere, including Switzerland. While the liver is most commonly affected, other organs can also be involved either by contiguity or haematogenous spread. To date, there is no epidemiological or clinical data on alveolar echinococcosis in the canton of Geneva.OBJECTIVES: To describe the demographic, epidemiological, clinical and therapeutic characteristics of alveolar echinococcosis in the canton of Geneva between 2010 and 2021.METHODS: An investigation was conducted among physicians from Geneva University Hospitals (HUG) and the private sector likely to encounter patients diagnosed with alveolar echinococcosis between 2010 and 2021. All patients being treated in the canton of Geneva were included. After obtaining their consent, an epidemiological questionnaire was completed by patients, and a clinical questionnaire by their referring physicians. Demographic, epidemiological and clinical data were entered into REDCap, then extracted and analysed.RESULTS: Of a total of 27 patients diagnosed with alveolar echinococcosis, 25 were included in the study; one patient did not provide his consent and one patient could not be contacted. The annual incidence of alveolar echinococcosis in the canton of Geneva was calculated at 0.24 cases per 100,000 inhabitants based on the subset (n = 14) domiciled in Geneva. The vast majority of patients (n = 24; 96%) were followed at HUG. The median age of patients was 55 years (range: 17–79) with a slight predominance of women (56%). Reported risk factors for alveolar echinococcosis included owning a vegetable garden (70.8%), often unfenced, practicing composting (69.6%), and owning a dog (58.3%) or a cat (58.3%). Four patients (16%) had an immunosuppressive condition. Only 52% of patients were symptomatic at the time of diagnosis. The liver was affected in most cases (n = 24; 96%), but one patient had a primary splenic location. Surgical resection for curative purposes was performed in 13 patients (52%). All patients received parasitostatic treatment with albendazole, discontinued in 5 patients (20%) due to drug-induced hepatitis. Three patients died (12%), of which two directly related to alveolar echinococcosis.CONCLUSION: Alveolar echinococcosis, a rare but severe disease, is endemic in the canton of Geneva. The establishment of mandatory reporting of this disease in Switzerland would allow monitoring of its epidemiological evolution. Primary and secondary prevention measures, currently non-existent, could potentially lower the incidence and severity of the disease.